Thailand as 2022 APEC Chair : what to expect - Pitakdumrongkit, Kaewkamol (2022)
Thailand has assumed the APEC Chair for 2022 and unveiled the theme of “Open. Connect. Balance.” How does the theme reflect the country’s interests and what are the likely APEC initiatives during its chairmanship?